ANALYSIS OF FACTORS AFFECTING THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK-EMKM) ON SHARIA-BASED MSMEs IN KUDUS REGENCY - ZULIYATI, ZULIYATI; INDRIANINGRUM, INDRIANINGRUM (IJIBE (International Journal of Islamic Business Ethics), 2021)
The purpose of this study is to analyze the effect of owner perceptions, education, socialization, business scale and business age on the application of the Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM) on sharia-based MSMEs in Kudus Regency. This study uses a quantitative research design, with the data used are primary data obtained from respondents through questionnaires, with the method of analysis using multiple linear regression analysis. A sample of 100 used purposive sampling technique with the criteria of Sharia-based MSMEs in Kudus Regency. The results showed that the variable owner perception, business scale, and business age had no effect on the application of SAK EMKM. Education and socialization have a positive effect on the implementation of SAK EMKM. The limitations of this study are that the independent variable is only able to influence the implementation of SAK EMKM by 28% and the object is only limited to sharia based MSMEs in Kudus Regency, so it cannot be generalized.